2017
DOI: 10.1089/mdr.2015.0359
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility and Molecular Screening of Class I Integron in Salmonella Isolates Recovered from Retail Raw Chicken Carcasses in China

Abstract: Salmonella is one of the leading causes for foodborne diseases. Foods, particularly those of animal origin, act as an important role for Salmonella transmission. In this study, the antibiotic susceptibility of 743 Salmonella isolates recovered from retail raw chicken carcasses in eight provinces was tested, and the isolates were also screened for the presence of class I integron and drug-resistant gene cassettes. One hundred thirteen (15.21%) isolates were harboring class I integron. A higher percentage of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Salmonella carrying class one integron int1 were found positive for multiple resistance genes. In this study, 20% isolates were found positive for the presence of the int1 gene, revealing the molecular basis of observed multidrug resistance [45]. These factors may facilitate the emergence of MDR pathogens.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Salmonella carrying class one integron int1 were found positive for multiple resistance genes. In this study, 20% isolates were found positive for the presence of the int1 gene, revealing the molecular basis of observed multidrug resistance [45]. These factors may facilitate the emergence of MDR pathogens.…”
Section: Discussionmentioning
confidence: 54%
“…These factors may facilitate the emergence of MDR pathogens. In many cases, resistance patterns are observed against those antimicrobials that are frequently used in veterinary practices [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Two such cassette arrays were embedded in simple integrons consisting of dfrA12 - orfF-aadA2 (1.9 kb, n = 4, Figure 3 I) and dfrA17-aadA5 (1.6 kb, n = 4, Figure 3 III), while the other two were embedded in complex integrons carrying the IS 26 element consisting of dfrA17-aadA5 -IS 26 (2.5 kb, n = 1, Figure 3 IV) and dfrA12-orfF- Δ aadA2 -IS 26 -Δ Tn3-orf (4 kb, n = 7, Figure 3 II). Array I and III in Figure 3 were popularly distributed in Salmonella (Li R. et al, 2013 ; Pérez-Moreno et al, 2013 ; Meng et al, 2017 ). Compared to Array I, aadA2 gene in Array II was truncated at the 578-bp from the 5′ CS by IS 26 , along with the insertion of a Δ Tn3-orf fragment and partial deletion of the qacE Δ 1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…The integrons are able to locate on either a chromosome or a mobile genetic element such as a plasmid (60). Several studies have stated that the integrons harboring aadA or a variant of aadA genes are common among Salmonella species (10,(61)(62)(63). The variable parts of integrons might be composed of variants of aad, dfr, or bla genes that contribute to aminoglycoside, sulfonamide, and cephalosporin resistance, respectively (10,61).…”
Section: Figmentioning
confidence: 99%
“…Several studies have stated that the integrons harboring aadA or a variant of aadA genes are common among Salmonella species (10,(61)(62)(63). The variable parts of integrons might be composed of variants of aad, dfr, or bla genes that contribute to aminoglycoside, sulfonamide, and cephalosporin resistance, respectively (10,61). S. enterica serotype Worthington detected in our study is commonly found in poultry, poultry products, and the environment in several parts of the world and harbors integrons either on the chromosome or plasmids (62,(64)(65)(66).…”
Section: Figmentioning
confidence: 99%